Taqwa Sharing Knowledge Integration: Menghilangkan hambatan untuk meningkatkan Inovasi dan Daya Saing - Anggraeni, Fadjar Setiyo (Lembaga Kajian dan Penerapan Nilai - Nilai Islam Unissula, 2024)
AbstractThere is still little empirical research that has been conducted on the impact of internal and external integration on the innovative capabilities of companies and competitive advantage through shared knowledge. Barriers to the KM process hinder the generation, storage, distribution and application of knowledge, which in turn will hinder OL. This study aims to combine the concepts of internal knowledge sharing, coopetition and the concept of external knowledge integration, as well as organizational learning capabilities by controlling barriers to the knowledge management process to produce innovation and increase organizational competitiveness and become a characteristic of a new leader. Using a critical review approach, we combine it with the Islamic worldview, namely taqwa, so that a single stone concept emerges which we call Taqwa Sharing Knowledge Integration. The birth of this new concept will have an impact on the birth of a leader who is able to overcome obstacles and invite people inside and outside the organization to share knowledge and be able to capture and integrate their knowledge to be processed into innovation and increase competitiveness based on taqwa.